Frontispiece: Simple but Efficient Method for Inhibiting Sintering and Aggregation of Catalytic Pt Nanoclusters on Metal‐Oxide Supports. Issue 7 (31st January 2017) - Koizumi, Kenichi; Nobusada, Katsuyuki; Boero, Mauro
Abstract : Heterogeneous Catalysis First‐principle molecular dynamical simulations enhanced by a free‐energy sampling technique demonstrated the inhibition of the sintering of nickel‐doped platinum clusters on metal oxides. The results reported by Nobusada et al. in their Full Paper onpage 1531 ff. pave a viable route to produce cost‐effective and sintering‐preventing platinum‐based nanoclusters without spoiling the catalytic efficiency, thus helping to reduce problems of air pollution. Their work is also an example of computer‐aided in silico design of catalysts.